ASSISTANCE IN CREATING A BUSINESS IDENTIFICATION NUMBER THROUGH THE ONLINE SINGLE SUBMISSION WEB - Siti Khoiriyah; Uswatun Khasanah; M. Pudail (Khidmatan, 2023)
Currently, the central government and local governments offer a lot of assistance, in the form of reduced costs in business assistance and training for business behavior, thus requiring business owners to have a Business Identification Number. Business Identification Number or NIB is the identity of a business actor issued by the government through the website of the OSS institution after the entrepreneur is registered. This status replaces several previous permits and is one of the prerequisites for obtaining a SIUP (Trade Business Permit). The method used is (Participatory Action Research) assistance carried out by researchers (1) Facilitator, (2) Animator, and (3) Initiator. Assistance in making NIB in Gondangan Hamlet and carried out from 21 August 2022 to 25 August 2022. This NIB can help MSMEs in Gondangan Hamlet to obtain business legality in order to facilitate the processing of other business letters, and show that the business does exist, operates and is feasible stand up. After being registered with 18 NIBs in Gondangan Hamlet, MSMEs in Gondangan Hamlet will be more advanced.